Batman - Adams, Neal 1941-2022
"The first of a planned three volume set chronologically compiling the legendary Batman work of Neal Adams. The first volume contains Adams's complete run from 1967-69: Batman #200, #203 and #210; The Brave and The Bold #75-76 and #79-85; Detective Comics #370, #372, #385, #389, #391, and #392; and World's Finest Comics #174-176, #178-180, #182-183, #185, and #186. Included is a new cover, an introduction by Adams, and an update and re-coloring of some of his early art." --Provided by publisher